2020
DOI: 10.1177/1178223420929702
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nail Lacquer on Taxane-Induced Nail Changes in Women With Breast Cancer

Abstract: Objective: Taxane-induced nail changes are considered as an important cosmetic manifestation with an incidence that reaches up to 44% of patients treated with taxane-included therapeutic regimens. In this article, we represent a clinical observational study to evaluate the effect of cosmetic nail lacquer on taxane-induced nail changes in female patients diagnosed with breast cancer. Methods: Prospectively, we identified those women who were diagnosed with breast cancer, scheduled to have AC-Taxol protocol. Any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Variability in chemotherapy regimens across studies emphasizes the impact of specific drugs on nail toxicity. Alshari et al 11 investigated using nail lacquer to mitigate taxane-induced nail changes and demonstrated its effectiveness. While nail lacquer offers a non-invasive protective measure, it requires regular application, which may not be convenient for all patients.…”
Section: Pacific Rim Int J Nurs Res • July-september 2024mentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in chemotherapy regimens across studies emphasizes the impact of specific drugs on nail toxicity. Alshari et al 11 investigated using nail lacquer to mitigate taxane-induced nail changes and demonstrated its effectiveness. While nail lacquer offers a non-invasive protective measure, it requires regular application, which may not be convenient for all patients.…”
Section: Pacific Rim Int J Nurs Res • July-september 2024mentioning
confidence: 99%
“…Such pain and discomfort substantially diminish patients' quality of life, often impeding their ability to perform daily functions. 3,11 Therefore, effective management of chemotherapyinduced nail toxicity is essential to minimize adverse complications and enhance patients' quality of life. 12 Hence, this study was conducted in Thailand among women undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…El 44% de las supervivientes sufre una decoloración en las uñas y problemas con las mismas, tanto en las manos como en los pies, en la mayoría de los casos estos inconvenientes ungueales suelen desaparecer tras la finalización del tratamiento, pero durante el mismo pueden provocar lesiones dolorosas que pueden afectar a diversas funciones, que van desde hematomas hasta la separación del lecho ungueal llamado onicólisis, no existe ningún tratamiento para la mejora de estas manifestaciones aunque el lavado de las mismas y el no uso de sustancias tóxicas como productos de limpieza o pinta uñas son las mejores estrategias de prevención [77].…”
Section: Menarquia Precozunclassified